Diversity loss with persistent human disturbance increases vulnerability to ecosystem collapse - MacDougall, A. S.; McCann, K. S.; Gellner, G.; Turkington, R. (Nature (London), 2013)
Persistent anthropogenic disturbance is shown simultaneously to drive plant species loss and stabilize some attributes of ecosystem function, analogous to a high-yield, low-diversity agricultural system, but increase the likelihood of irreversible collapse after sudden environmental change. Burning issue: a high price for diversity loss Stretches of oak savanna in the Pacific Northwest of North America have been subject to fire-prevention measures since the mid-nineteenth century. The resulting grassland has lost plant species but achieves stable high-yield annual production — rather like a high-yield agricultural system — and remains resilient to invasive species and climate fluctuation. A long-term study in which selected grassland plots were periodically burned and allowed to recover now demonstrates the critical value of biodiversity when ecosystems experience disturbance. Grasslands were able to recover from burning only in areas that had a relatively high diversity of native plants. This work demonstrates how persistent human activity can homogenize both structure and function of an ecological system, while weakening the diversity-related mechanisms needed to compensate for sudden disturbance. There are many terrestrial systems today that have become homogenized by persistent human activity that may be similarly vulnerable to sudden environmental change that will be only evident after the collapse occurs. Long-term and persistent human disturbances have simultaneously altered the stability and diversity of ecological systems, with disturbances directly reducing functional attributes such as invasion resistance, while eliminating the buffering effects of high species diversity 1 , 2 , 3 , 4 . Theory predicts that this combination of environmental change and diversity loss increases the risk of abrupt and potentially irreversible ecosystem collapse 1 , 2 , 3 , 5 , 6 , 7 , but long-term empirical evidence from natural systems is lacking. Here we demonstrate this relationship in a degraded but species-rich pyrogenic grassland in which the combined effects of fire suppression, invasion and trophic collapse have created a species-poor grassland that is highly productive, resilient to yearly climatic fluctuations, and resistant to invasion, but vulnerable to rapid collapse after the re-introduction of fire. We initially show how human disturbance has created a negative relationship between diversity and function, contrary to theoretical predictions 3 , 4 . Fire prevention since the mid-nineteenth century is associated with the loss of plant species but it has stabilized high-yield annual production and invasion resistance, comparable to a managed high-yield low-diversity agricultural system. In managing for fire suppression, however, a hidden vulnerability to sudden environmental change emerges that is explained by the elimination of the buffering effects of high species diversity. With the re-introduction of fire, grasslands only persist in areas with remnant concentrations of native species, in which a range of rare and mostly functionally redundant plants proliferate after burning and prevent extensive invasion including a rapid conversion towards woodland. This research shows how biodiversity can be crucial for ecosystem stability despite appearing functionally insignificant beforehand, a relationship probably applicable to many ecosystems given the globally prevalent combination of intensive long-term land management and species loss.